Analysis of the Effect of Road Damage Conditions on Vehicle Speed (Case Study of Road Sections in Tanjungbalai City) - Sihombing, Alexander Tuahta (PT Inovasi Pratama Internasional, 2024)
Economic growth and technological advancements have increased mobility in various aspects of life, with land transportation being the primary choice for daily activities. In this context, the availability of good road infrastructure is crucial for ensuring the smooth operation of transportation systems. The condition of road pavement is a key factor that influences how efficiently the system operates, as poor pavement conditions can lead to longer vehicle travel times. A comprehensive analysis can help identify specific components that contribute to changes in road conditions over time. According to the Road Law (2004), public roads are classified based on their function into arterial roads, collector roads, local roads, and environmental roads, each with different characteristics in terms of travel distance and average speed. Road damage is generally divided into structural damage, which occurs when the pavement can no longer support traffic loads, and functional damage, which compromises the safety and comfort of road users, thereby increasing operational costs. Several factors contributing to road pavement damage include increased traffic loads, poor drainage systems, construction materials, unstable subgrade conditions, and Indonesia's tropical climate, characterized by high air temperatures and rainfall. Research conducted in Tanjung Balai City shows a correlation between road pavement conditions and vehicle speed; as pavement conditions deteriorate, vehicle speeds decrease. The results indicate a significant relationship, with an R2 value of 0.92, meaning a 92 percent correlation.